Roller girl - Jamieson, Victoria (Dial Books for Young Readers, an imprint of Penguin Group (USA) LLC : Scholastic Inc., 2015)
"A graphic novel adventure about a girl who discovers roller derby right as she and her best friend are growing apart"--Provided by publisher.